Strategy Kampanye Gerakan #BijakBerplastik PT Danone Aqua Dalam Merayakan Hari Lingkungan Hidup Sedunia 2018 - Siti Qonaah (Universitas Bina Sarana Informatika, 2019)
World Environment Day (WED) is the largest environmental preservation campaign in the world and commemorated on June 5, 2018 with the theme